Intravaginal delivery for CRISPR–Cas9 technology: For example, the treatment of HPV infection. Issue 2 (12th February 2023) - Zhen, Shuai; Chen, Hong; Lu, Jiaojiao; Yang, Xiling; Tuo, Xiaoqian; Chang, Shixue; Tian, Yuhan; Li, Xu
Abstract: The increasing incidence of sexually transmitted diseases in women, including human papillomavirus (HPV) infection, has led to the need to develop user‐friendly potential prevention methods. At present, although there are several therapeutic parts, none of them has a preventive effect, but they are only limited to providing patients with symptom relief. Researchers have now recognized the need to find effective local preventive agents. One of the potential undiscovered local fungicides is the vaginal delivery of CRISPR/Cas9. CRISPR/Cas9 delivery involves silencing gene expression in a sequence‐specific manner in the pathogenic agent, thus showing microbicidal activity. However, vaginal mucosal barrier and physiological changes (such as pH value and variable epithelial thickness in the menstrual cycle) are the main obstacles to effective delivery and cell uptake of CRISPR/Cas9. To enhance the vaginal delivery of CRISPR/Cas9, so far, nano‐carrier systems such as lipid delivery systems, macromolecular systems, polymer nanoparticles, aptamers, and cell‐penetrating peptides have been extensively studied. In this paper, various nano‐carriers and their prospects in the preclinical stage are described, as well as the future significance of CRISPR/Cas9 vaginal delivery based on nano‐carriers.